Violence at Verteba Cave, Ukraine: New insights into the Late Neolithic intergroup conflict. (20th November 2017) - Madden, G.D.; Karsten, J.K.; Ledogar, S.H.; Schmidt, R.; Sokhatsky, M.P.
Abstract: Many researchers have pointed to the huge "megasites" and construction of fortifications as evidence of intergroup hostilities among the Late Neolithic Tripolye archaeological culture. However, to date, very few skeletal remains have been analysed for the types of traumatic injury that serve as direct evidence for violent conflict. In this study, we examine trauma on human remains from the Tripolye site of Verteba Cave in western Ukraine. The remains of 36 individuals, including 25 crania, were buried in the gypsum cave as secondary interments. The frequency of cranial trauma is 30–44% among the 25 crania, 6 males, 4 females, and 1 adult of indeterminate sex displayed cranial trauma. Of the 18 total fractures, 10 were significantly large and penetrating, suggesting lethal force. Over half of the trauma is located on the posterior aspect of the crania, suggesting that the victims were attacked from behind. Sixteen of the fractures observed were perimortem and 2 were ante‐mortem. The distribution and characteristics of the fractures suggest that some of the Tripolye individuals buried at Verteba Cave were victims of a lethal surprise attack. Resources were limited due to population growth and migration, leading to conflict over resource access. It is hypothesised that during this time of change, burial in this cave aided in development of identity and ownership of the local territory.